Prevalence of Helicobacter pylori in Pregnancy related to birth weight and micronutrient deficiency (Eurasian Medical Research Periodical, 2022)
Infection with the bacterium Helicobacter pylori is common, especially in underdeveloped regions. hyperemesis gravidarum, foetal neural tube abnormalities, and other pregnancy-related complications. Miscarriage and stunted foetal development that occurs within the uterus. In this study, we aimed to collect evidence of how H. pylori infection affects Low-income mothers' risk of having babies with low birth weight, nutritional deficiencies, and anaemia on unfavourable results during pregnancy. Of critical importance, there are Problems with our current knowledge of how H. pylori infection and stomach problems are connected caused by aninsufficiency of essential nutrients during pregnancy.. Methods: In iraq, researchers used a prospective cohort design to examine participants' health histories between July 2020 and July 2021. The Individuals included both first-time and repeatmothers who tested negative for hepatitis due to either a positive or negative H. pylori result on a hepatitis screen. Participants were recruited at 18 weeks' gestation, and they were evaluated again at 13 and 18 weeks. period of time between the weeks before labour and the days after it.Stool H. pylori antigen testing was used to confirm the presence of H. pylori infection. Maternal Body mass index (BMI) and total weight increase during pregnancy were determined by taking measurements of height and weight. The study included only full-term, healthy newborns. Those with a birth weight of less than 2,500 grammes were considered to have a low birth weight (LBW).Results: The average age of the 110 registered individuals was 20.9 2.7 years (SD = 4.9 years). Births occurred at a mean SD gestational age of 39.4 1.0 weeks. There were 61.5% (n = 94) primates and 52.9% One hundred and eighty-eight people tested positive for H. pylori infection. Weight-for-height ratio (WHR) was (14.6%) were short (n = 14), whereas 38.2% were tall (n = 36). As a percentage of newborns, Low birth weight (2500 g) was seen in 13.6% (n = 13) of the study population. Having a mother who tested positive for H. pylori was a significant predictor of LBW (odds ratio [OR], 3.60, 95% CI, 2.70–5.10). 3.4, 95% CI 1.4-8.2; P = 0.008) and maternalheight at recruitment 156 cm (OR 1.1, 95% CI 1.1-11.5; P = 0.031) and maternal height at recruitment 156 cm (OR 3.4, 95% pregnant women who gain less than 0.3 kg per week during the second and third trimesters (OR 3.8, 95% CI 1.0-14.1; P = 0.044).Conclusion H. pylori infection is linked to LBW in both first-time and repeat mothers, we conclude. Infection with H. pylori has been linked to risk of IDA rises, although not always in tandem with other nutritional During pregnancy, vitamins are essential.